Design Analysis of Driven Pile Foundations of Retaining Walls in Granular Soils - Suradi, Muhammad; Nabi, Abdul; Hasanuddin, Haeril Abdi; Muktadiru, Andi Muhammad; Ridhatullah, Agung (INTEK: Jurnal Penelitian, 2016)
The aim of this paper is to investigate the effect of the pile of retaining wall design parameters including slope height and soil shear strength on the depth of driven piles. Parametric study was performed by varying the slope height and internal friction angle of granular soils in order to investigate the effect of these parameters on the pile depth. This study indicated that the pile depth increased more significantly with the increase of slope height for low internal friction angle (7,69 m for ϕ = 20º) than those for high internal friction angle (3,87 m for ϕ = 40º) with the increase of slope height from 2 m to 10 m. Meanwhile this study showed larger increase of the pile depth (2.86 m) for the dcrease in internal friction angle when slope soils and subgrade have the same internal friction angle than those when they have different internal friction angle (1.41 m) for 6 m in the slope height with the decrease of internal friction angle of soils from ϕ = 40º to 20º.